Building reputation through sustainable supplier selection: the case of an emerging economy - Mohammad Asif Salam; Murad Ali (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this research is to examine the drivers of sustainable supplier selection (SSS) and investigate the extent to which it is associated with a buyer's financial performance within an emerging economy context. Design/methodology/approach The data were collected from 235 supply chain and procurement professionals in Thailand. The structural relationship was tested using partial least squares based structural equation modeling (PLS-SEM) and PROCESS tool. Findings Based on the empirical findings, firms that pursue sustainability initiatives during supplier selection process enjoy better financial performance than their competitors. The analysis suggests six hypothetical paths explain SSS. Suppliers' human rights and safety focus are the most powerful determinants of SSS. Significantly, positive support was found for the SSS and buyers' financial performance relationship. Finally, there is a significant moderating effect of resource investment on sustainability efforts. Research limitations/implications Data for the study were collected from a single industry, so the findings are indicative but not representative of all supply chains. Due to this limitation, the findings cannot be generalized across other countries and industries. This study is a starting point in understanding the role of SSS in creating a sustainable supply chain. Future research may develop a comprehensive understanding of the nature and magnitude of the impact of SSS on sustainable supply chains. Originality/value This paper contributes toward an understanding of the determinants of SSS and its consequences for sustainable supply chains.
Keywords: 650; Sustainable supplier selection; Purchasing social responsibility; Financial performance; Supply chain management; Stakeholder theory